A escola enquanto espaço privilegiado de construção de "meninos de verdade" :concepções e valores atribuidos a essa instituição por crianças pobres - Santos, Waleska Patrícia de Lima (2004)
The intention of this study was to identify the school conception (conceptions) in the discourse of poor children. There were inquired two groups of subjects: the first was composed of children that inserted precociously themselves into the work market and must to go to school because they take part in one of the governmental programs, called, minimum income programs. The second will be composed of children that live in the poorest district in Natal/RN city. And don´t have obligatoriness to go to school. Thus, thematics like precocious work, minimum income program, capitalism, neoliberalism was aproached in our discussion. We also intended to make a illustrate with Pinochio Adventures fable, because its conception school is similar like real official discourse school from everybody. In cited narrative, the character Gepeto didn t know what s a truth child but knows that exist a place in city where his maledoll Pinochio would be one the school. Thus, this institution was destine by the justice and politics from Gepetos s city how children right. Pinochio, in the book s end, to be transformed himself in a truth child because learned in school responsible and goodness behaviors. To uphold our inquiry we used the Content Analysis and socio-historical perspectives. The result showed that the children know that exist differents schools: yours and other, to rich class. Their school is admited like good, it is a study place, it isn´t disorders place; and also make propotional to social ascencion. The children s discourses is similar to capitalism s discourse